2003
DOI: 10.5014/ajot.57.4.435
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy in Transitioning Adolescents to Post-Secondary Activities

Abstract: Occupational therapists in this study provided ancillary services to high school students with disabilities with greater emphasis on technology, task or environmental modification, and IEP or ITP planning, as perceived by special evaluation directors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
(20 reference statements)
3
14
0
Order By: Relevance
“…These results are similar to previous findings (Brandenburg-Shasby, 2005;Kardos & White, 2005;Orentlicher, 2007;Spencer et al, 2003). Even though respondents reported they feel occupational therapy has a role to play in secondary transition planning, the involvement of occupational therapy is not reflected in practice as seen in this study and previous occupational therapy literature (Brollier et al, 1994;Brandenburg-Shasby, 2005;Kardos & White, 2005;Orentlicher, 2007;Spencer et al, 2003). It suggests possible limitations of collaboration and communication between professionals and supports the notion that therapists in the schools tend to consider their intervention as remedial, taskoriented, and specialized versus a more holistic, person-centered model (Loukas et al, 2010;Orentlicher & Micheals, 2000a, 2000b, 2003a, 2003b.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…These results are similar to previous findings (Brandenburg-Shasby, 2005;Kardos & White, 2005;Orentlicher, 2007;Spencer et al, 2003). Even though respondents reported they feel occupational therapy has a role to play in secondary transition planning, the involvement of occupational therapy is not reflected in practice as seen in this study and previous occupational therapy literature (Brollier et al, 1994;Brandenburg-Shasby, 2005;Kardos & White, 2005;Orentlicher, 2007;Spencer et al, 2003). It suggests possible limitations of collaboration and communication between professionals and supports the notion that therapists in the schools tend to consider their intervention as remedial, taskoriented, and specialized versus a more holistic, person-centered model (Loukas et al, 2010;Orentlicher & Micheals, 2000a, 2000b, 2003a, 2003b.…”
Section: Discussionsupporting
confidence: 95%
“…Those who reported some involvement indicated minimal and inconsistent levels of involvement. These results are similar to previous findings (Brandenburg-Shasby, 2005;Kardos & White, 2005;Orentlicher, 2007;Spencer et al, 2003). Even though respondents reported they feel occupational therapy has a role to play in secondary transition planning, the involvement of occupational therapy is not reflected in practice as seen in this study and previous occupational therapy literature (Brollier et al, 1994;Brandenburg-Shasby, 2005;Kardos & White, 2005;Orentlicher, 2007;Spencer et al, 2003).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Occupational therapy (OT) supports students with special needs to participate successfully in secondary education and prepare for transitioning to postsecondary activities and adulthood (Copley, Turpin, Gordon, & McLaren, 2011;Gangl, Strecker Neufeld, & Berg, 2011;Juan & Swinth, 2010;Marczuk, Taff, & Berg, 2014;Passmore, 2004;Paul-Ward, 2009;Spencer, Emery, & Schneck, 2003). Whether working with students with disabilities, or who are in foster care, are refugees, or have experienced a disconnection from school, occupational therapists play a unique role in recognizing and addressing barriers that impede the students' full participation in meaningful occupations, such as pursuing PSE.…”
mentioning
confidence: 99%
“…Given the legal mandates of IDEA, the AOTA Standards for Practice, and the unmet transition needs of students with disabilities and their families, there seems to be a strong need to further utilize occupational therapists in transition evaluations and interventions. Research on school-based occupational therapy practice documents a general lack of involvement of occupational therapy practitioners in both transition planning (evaluation) and transition service delivery (intervention) (AOTA, 2000b;Arnold, 2000;Spencer et al, 2003). A survey of the members of AOTA (AOTA, 2000b), for example, reported that about 29% of all occupational therapists work in schools, with less than 16% of these therapists identifying themselves as working with special education students within the transition services agerange.…”
mentioning
confidence: 99%